The Design of Student Worksheet Problem based Learning to Improve Problem Solving Ability of the Eighth-Grade Students Junior High School in Indonesia - Akma, Tio; man, Supar (International Journal of Engineering and Technology, 2018)
The purpose of this research is to develop the design of the student worksheet Problem-Based Learning to improve the problem-solving ability of eighth-grade junior high school students. This research uses Four-D development model. The development procedure includes four stages: define, design, develop, and dissemination. The subjects of the study were eighth graders of junior high school 9 Yogyakarta, Indonesia. The object of this research is curriculum, student characteristics and evaluation of teaching materials. This research resulted in a) the results of needs analysis of student worksheet Problem Based Learning to improve problem-solving abilities appropriate to the curriculum, student characteristics, learning materials and objectives. b) the results of the Student Worksheet design consisting of the cover, introduction, table of contents, instructions manual, basic competence, supporting information, action steps, and exercise. This research can be continued to develop and dissemination.